Secondary Reserve Provision through a Smart Aggregation Strategy of Electric Vehicles - Guzman, Cindy P. [UNESP]; Romero, Ruben [UNESP]; Arias, Nataly Banol; Rider, Marcos J.; Franco, John Fredy [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The electric vehicles (EVs) are flexible loads that can be controlled to provide secondary reserve services (RSs) to transmission network operator (TNO) via charging or stop charging the batteries. An aggregator, as an intermediary agent between the EVs owners and the TNO, can schedule RSs through EV charging control. This paper proposes a smart aggregation strategy for the EV charging control that allows the aggregator's participation in the reserve market, while guaranteeing the energy required by the EVs for transportation. The smart strategy, based on a linear programming model, coordinates the charging of EVs, and allows offering RSs and selling energy produced by distributed generation units to maximize the aggregator's profit. Results for a case study with 1, 000 vehicles show that the strategy effectively contributes to the offering of RSs to the TNO, while satisfying the energy requirements of the EV owners.
Keywords: Aggregator; distributed generators; electric vehicles; electrical distribution system; secondary reserve market